FREQUENCY OF URINARY INCONTINENCE (UI) AND ITS ASSOCIATED RISK FACTORS IN PREGNANT POPULATION - Yaqub, Umaira; Habib, Maria; Shaheen, Talat (Pakistan Armed Forces Medical Journal, 2019)
Objective: To study the frequency of urinary incontinence and to identify its associated risk factors in pregnancy. Study Design: A descriptive cross sectional study.Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi, from Feb and Mar 2017. Material and Methods: A descriptive cross sectional study was conducted at tertiary care hospital of Pakistan on 399 pregnant women having antenatal care during third trimester of pregnancy. A well designed questionnaire gathered data on demographic variables, presence or absence of urinary incontinence (UI) in current pregnancy and its associated risk factors. Data were analyzed using SPSS version 20. Descriptive statistics and logistic regression analysis were performed. A p